Komponen Senyawa Aktif pada Udang Serta Aplikasinya dalam Pangan - Ngginak, James; Semangun, Haryono; Mangimbulude, Jubhar C.; Rondonuwu, Ferdy S. (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
Indonesian water area is vast and has a great potential of natural resources. Most of the Indonesian people working as fisherman describes that oceanis place of making a living. Watery area resources Indonesian watery area is vast and has a great potential incude shrimps, fish, and other organism tosupport human life. Ocean organism has been known to contain nutrition which is good for human’s health. Shrimps contains omega 3, mineral, fat,citin, carotenoide (astaxanthin) and vitamin. The active compound have an ability to prevent disease and meet the nutritional need of body. Omega3 andastaxantin for example are active compounds found in shrimps. These compound play a role as antioxidant and free radicals scavenger can be supplementfor pregnant women and baby. Omega 3 and antaksantine are found in various shrimps and fish. Thus, the development of product from this organismincludes supplement, margarine, cake, souse, bread, kerupuk, flour and salt. In this review, the writer describes the the functional compound and itsusage as food product.